THE DEIXIS ANALYSIS IN BRUNO MARS’S DOO WOPS AND HOOLIGANS ALBUM SONG LYRICS - Nadila Puspita Yanti; Hajjah Zulianti; Natasha Aurellia (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
The study aims to determine deixis types and the singer's intentions in the lyrics of Bruno Mars' songs from the album "Doo-Wops and Hooligans" (2010). As a source of data to complete this study, the researchers used ten songs from the album. This study uses qualitative methods to complement the research data. While collecting data, the researchers used listening and note-taking strategies. The researcher also applies Alan Cruse’s theory to analyze the types of deixis from singers in Bruno Mars' song lyrics on the album "Doo-Wops and Hooligans" (2010). The findings of this study include deixis types such as personal deictic, spatial deictic, temporal deictic, social deictic, and discourse deictic. First, personal deixis discovered 75 deixis words (27%); second, spatial deixis discovered 39 deixis words (14%); third, temporal deixis discovered 34 deixis words (12%); fourth, social deixis discovered 22 deixis words (8%); while discourse deixis discovered 113 deixis words (40%). This research has implications for the singer's motives and intentions in the songs on the album "Doo-Wops and Hooligans" (2010) by Bruno Mars. Such implications include admiration, romance, friendship, sadness, disappointment, laziness, drunkenness, falling in love, despair, and freedom.